Extradigestive Manifestations of Helicobacter Pylori Infection - An Overview 2016
DOI: 10.5772/63827
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Extradigestive Manifestations of Helicobacter pylori Infection in Childhood

Abstract: Helicobacter pylori infects more than % of the world population and is acquired in infancy. Higher prevalence is found in developing countries, and within geographic areas the predominance correlates inversely with socioeconomic status, especially with living conditions during childhood. Initially, in adults, H. pylori was only associated with gastric diseases, such as peptic ulcer, gastritis, gastric adenocarcinoma, and gastric mucosa-associated lymphoid tissue M"LT lymphoma, and in childhood, with chronic ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 121 publications
(403 reference statements)
0
5
0
Order By: Relevance
“…H. pylori bacteria sequester and interfere with the iron absorption following the H. pylori-associated chronic gastritis [56] may lead to the lowering of Hb concentration in H. pylori-infected individuals. Moreover, hemorrhagic gastritis-dependent iron loss [57] and actively bleeding peptic ulceration may also contribute to depression in the Hb level of H. pylori-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori bacteria sequester and interfere with the iron absorption following the H. pylori-associated chronic gastritis [56] may lead to the lowering of Hb concentration in H. pylori-infected individuals. Moreover, hemorrhagic gastritis-dependent iron loss [57] and actively bleeding peptic ulceration may also contribute to depression in the Hb level of H. pylori-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of RBC parameters in H. pylori -infected adult patients associated with different mechanisms; consumption of iron by the H. pylori 30 decreased iron absorption secondary to chronic gastritis, 20 iron loss via hemorrhagic gastritis, and active bleeding peptic ulcers, deficiency of iron and vitamin B12 secondary to chronic and atrophic gastritis, 27 which might contribute to the alteration of RBC parameters in H. pylori -infected patients as compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in line with other similar studies conducted in Palestine in adult H. pylori -infected patients, 17 in Egypt 22 and Karachi. 38 Consumption of iron by the H. pylori , 30 decreased iron absorption secondary to chronic gastritis, 20 iron loss via hemorrhagic gastritis, and active bleeding peptic ulcers, 27 which might contribute to decrement of blood hemoglobin concentration in H. pylori -infected patients. Several studies reported that depletion of iron in H. pylori -infected patients, 30 and eradication of H. pylori infection shows improvements in blood hemoglobin concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was discovered by two pathologists in 1982: Barry Marshall and Robin Warren, who were awarded a Nobel Prize in the indicated year. 1 H. pylori has been recognized as a major human pathogen for approximately four decades. 2 H. pylori infection is formally recognized as an infectious disease, an entity that is now included in the International Classification of Diseases 11th Revision.…”
Section: Introductionmentioning
confidence: 99%